Polymorphism in Molecular Crystals. - Bernstein, Joel (International Union of Crystallography - Monographs on Crystallography, No. 14., 2007)
This book deals with polymorphism - the existence of different solid structures of the same chemical entity (for example graphite and diamond, both composed of carbon) which provide ideal systems for investigating the relationship between the structure and properties of a wide variety of materials. - ;Polymorphism - the multiplicity of structures or forms - is a term that is used in many disciplines. In chemistry it refers to the existence of more than one crystal structure for a particular chemical substance. The properties of a substance are determined by its composition and by its structure.